2021
DOI: 10.3390/ijms22084106
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Disorder, a Key Pathogenesis of HCMV-Related Diseases

Abstract: Human cytomegalovirus (HCMV) belongs to the β-herpesvirus family, which is transmitted in almost every part of the world and is carried by more than 90% of the general population. Increasing evidence indicates that HCMV infection triggers numerous diseases by disrupting the normal physiological activity of host cells, particularly apoptosis. Apoptosis disorder plays a key role in the initiation and development of multiple diseases. However, the relationship and molecular mechanism of HCMV-related diseases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 114 publications
0
14
0
Order By: Relevance
“…Human cytomegalovirus is inherited by more than 90% of the general population. 81 In healthy adults, HCMV infection is often benign, but in infants with perinatal infection and in those with diminished immune systems, it can result in serious morbidity. It is found that the increase of SphK1 activity and the decrease of S1P degradation activity in HCMVinfected cells.…”
Section: Human Cytomegalovirusmentioning
confidence: 99%
See 1 more Smart Citation
“…Human cytomegalovirus is inherited by more than 90% of the general population. 81 In healthy adults, HCMV infection is often benign, but in infants with perinatal infection and in those with diminished immune systems, it can result in serious morbidity. It is found that the increase of SphK1 activity and the decrease of S1P degradation activity in HCMVinfected cells.…”
Section: Human Cytomegalovirusmentioning
confidence: 99%
“…The population is susceptible to the herpetic virus referred to as human cytomegalovirus (HCMV). Human cytomegalovirus is inherited by more than 90% of the general population 81 . In healthy adults, HCMV infection is often benign, but in infants with perinatal infection and in those with diminished immune systems, it can result in serious morbidity.…”
Section: The Relationship Between Virus Replication and Sphingosine‐1...mentioning
confidence: 99%
“…It is certain that proper apoptosis helps to maintain the normal function of the body, while dysregulation of apoptosis causes serious consequences. 67 Tubular epithelial cells and podocytes are important cells in the kidney that perform reabsorption and filtration functions. Their excessive apoptosis is closely related to the occurrence and development of renal diseases.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In fact, there is a fine balance in the amount of apoptosis that should occur in different tissues at all developmental stages. For example, both excess or insufficient apoptosis has been shown to result in common and debilitating diseases such as Alzheimer’s, Parkinson’s, rheumatoid arthritis, viral infection (such as coronaviruses, HIV, herpes), and carcinogenesis [ 18 , 19 , 20 , 21 , 22 , 23 ]. Apoptosis can be initiated both intrinsically and extrinsically by a variety of signals, where intrinsic apoptosis involves mitochondria and mitochondrial machinery [ 24 ] and extrinsic apoptosis is mediated by activation of transmembrane death receptors (which are part of the tumor necrosis factor (TNF) family) [ 25 , 26 ].…”
Section: Non-ionizing Radiation and Control Of Cellular Processesmentioning
confidence: 99%